Modalities of visually locating the intervention areas in the restoration documentation - Bogdan Gavrilean (Anastasis: Research in Medieval Culture and Art, 2016)
: The aim of the present article is to present modalities of visually locating the areas of specific intervention within heritage buildings, using vector graphics and bitmap image software, employed in the framework of preservation-restoration documentation.